Association between endotypes of prematurity and pharmacological closure of patent ductus arteriosus: A systematic review and meta-analysis - Gonzalez-Luis, Gema E; Borges-Lujan, Moreyba; Villamor, Eduardo (Frontiers in Pediatrics, 2023)
Endotypes leading to very and extremely preterm birth are clustered into two groups: infection/inflammation and dysfunctional placentation. We conducted a systematic review of observational studies exploring the association between these two endotypes and the pharmacological closure of patent ductus arteriosus (PDA) induced by cyclooxygenase (COX) inhibitors. Chorioamnionitis represented the infectious-inflammatory endotype, while dysfunctional placentation proxies were hypertensive disorders of pregnancy (HDP) and small for gestational age (SGA) or intrauterine growth restriction. PubMed/Medline and Embase databases were searched. The random-effects odds ratio (OR) and 95% confidence interval (CI) were calculated for each association. We included 30 studies (12639 infants). Meta-analysis showed a significant association between exposure to HDP and increased rate of pharmacological closure of PDA (17 studies, OR 1.41, 95% CI 1.10-1.81, p=0.006). In contrast, neither chorioamnionitis (13 studies, OR 0.75, 95% CI 0.47-1.18, p=0.211) nor SGA (17 studies, OR 1.20, 95% CI 0.96-1.50, p=0.115) were significantly associated with the response to therapy. Subgroup analyses showed that the higher response to COX inhibitors in the HDP group was significant for indomethacin (OR 1.568, 95% CI 1.147-2.141, p=0.005) but not for ibuprofen (OR 1.107, 95% CI 0.248-4.392, p=0.894) or for the studies using both drugs (OR 1.280, 95% CI 0.935-1.751, p=0.124). However, meta-regression showed that this difference between the drugs was not statistically significant (p=0.404). In conclusion, our data suggest that the pathologic condition that triggers prematurity may alter the response to pharmacological treatment of PDA. The DA of infants exposed to HDP appears to be more responsive to COX inhibitors.